A harmonized approach to intracellular cytokine staining gating: Results from an international multiconsortia proficiency panel conducted by the Cancer Immunotherapy Consortium (CIC/CRI). Issue 8 (20th June 2013) - McNeil, Lisa K.; Price, Leah; Britten, Cedrik M.; Jaimes, Maria; Maecker, Holden; Odunsi, Kunle; Matsuzaki, Junko; Staats, Janet S.; Thorpe, Jerill; Yuan, Jianda; Janetzki, Sylvia
<x xml:space="preserve">Abstract</x> Previous results from two proficiency panels of intracellular cytokine staining (ICS) from the Cancer Immunotherapy Consortium and panels from the National Institute of Allergy and Infectious Disease and the Association for Cancer Immunotherapy highlight the variability across laboratories in reported % CD8+ or % CD4+ cytokine‐positive cells. One of the main causes of interassay variability in flow cytometry‐based assays is due to differences in gating strategies between laboratories, which may prohibit the generation of robust results within single centers and across institutions. To study how gating strategies affect the variation in reported results, a gating panel was organized where all participants analyzed the same set of Flow Cytometry Standard (FCS) files from a four‐color ICS assay using their own gating protocol (Phase I) and a gating protocol drafted by consensus from the organizers of the panel (Phase II). Focusing on analysis removed donor, assay, and instrument variation, enabling us to quantify the variability caused by gating alone. One hundred ten participating laboratories applied 110 different gating approaches. This led to high variability in the reported percentage of cytokine‐positive cells and consequently in response detection in Phase I. However, variability was dramatically reduced when all laboratories used the same gating strategy (Phase II). Proximity of the cytokine gate to the negative population most impacted true‐positive and false‐positive response detection. Recommendations are provided for the (1) placement of the cytokine‐positive gate, (2) identification of CD4+ CD8+ double‐positive T cells, (3) placement of lymphocyte gate, (4) inclusion of dim cells, (5) gate uniformity, and 6) proper adjustment of the biexponential scaling. © 2013 International Society for Advancement of Cytometry